The Potential of Pregabalin in Neurology, Psychiatry and Addiction: A Qualitative Overview - Martinotti, Giovanni; Lupi, Matteo; Sarchione, Fabiola; Santacroce, Rita; Salone, Anatolia; De Berardis, Domenico; Serroni, Nicola; Cavuto, Marilde; Signorelli, Maria; Aguglia, Eugenio; Valchera, Alessandro; Iasevoli, Felice; et al. (Current Pharmaceutical Design, 2013)
Pregabalin is an anticonvulsant drug that binds to the α2δ(alpha2delta) subunit of the voltage-dependent calcium channel in central nervous system (CNS). Pregabalin decreases the release of neurotransmitters, including glutamate, norepinephrine, substance P and calcitonin gene-related peptide. Purpose of this paper is to offer a qualitative overview of the studies currently available in literature about this drug, examining the effectiveness of pregabalin in its various fields of application. Our analysis, conducted on a final selection of 349 scientific papers, shows that pregabalin may help to reduce pain in diabetic neuropathy, in post-herpetic neuralgia and in some patients affected by fibromyalgia. It is also effective for the treatment of diverse types of seizures and has similar efficacy to benzodiazepines and venlafaxine in anxiety disorder. Moreover, pregabalin may be a therapeutic agent for the treatment of alcohol abuse, in both withdrawal phase and relapse prevention. Possible implications in the treatment of benzodiazepines dependence are emerging, but a potential abuse or misuse of the drug has also been reported. Range of dosage may fluctuate considerably, from 75 mg to 600 mg per day. Further studies are needed to completely understand pregabalin mechanism of action in the different diseases.
Keywords: anxiety